Analisis Tingkat Minat, Motivasi, dan Kesadaran Akan Hidup Sehat Masyarakat Dalam Melaksanakan Aktivitas Olahraga di Kota Padang - Yasir, Luthfi Zahira; Gemaini, Andri; Welis, Wilda; Permata Sari, Anggun (Jurnal IKEOR, 2024)
The absence of data on the fitness level of people who carry out sports activities in Padang City is one of the drivers for the author to conduct research on the interest, motivation and awareness of healthy living of people who carry out sports activities in Padang City. This study want to know about interest, motivation, and awareness of healthy living of people in doing sports activities in Padang City. Descriptive quantitative is the type of research in this study. In this study, the population is the perople of Padang City who carry out sports activities at FIK UNP Field, Wirabraja Field, Gor H. Agus Salim Field, and Padang City Hall. The research sample amounted to 100 people who carried out sports activities which were taken with incidental nonprobability sampling techniques. The data is getting by uses a quistionnaire. Techniques for analysis the data is uses descriptive percentage analysis. The results showed that community interest in carrying out sports activities in Padang City is very high with an overall percentage score of 86.49. Community motivation in carrying out sports activities in Padang City is very high with an overall percentage score of 85.69%. Awareness of healthy living in the community in carrying out sports activities in Padang City is very high with an overall percentage score of 85.79%.